PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN AUDIO VISUAL TERHADAP HASIL BELAJAR PADA PEMBELAJARAN PKN SISWA KELAS VB SDN SUNGGUMINASA V - Suardi; Musdalifah Syahrir, Nur Khalis.T (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of using audio-visual learning media on the learning outcomes of Civics Education (Pancasila Education) among fifth-grade students at SDN Sungguminasa V. The research problem is: